Economic impact of Hafnarhólmi Bird Colony in Borgarfjörður Eystri; Hafnarhólmi í Borgarfirði eystri - Efnahagsleg áhrif - Jukka Siltanen (University of Iceland, Institute of Economic Studies (IoES), 2019)
The tourism boom that started in 2011 shortly after the Eyjafjallajökull eruption has changed Iceland in many ways. Economically tourism has quickly become the country's main export sector. Livelihoods and communities have changed with the influx of foreign tourists and workers. Tourism has also exerted environmental pressures and degradation at many popular sites. At the same time, tourism has put new emphasis on the value of Iceland's natural attractions and environmental conservation as most visitors come to Iceland to experience the unique nature. The perception of protected areas as 'economical dead space' or sinks of public money have started to change towards potential sources of income and employment opportunities. To assess these opportunities, many techniques to measure economic impacts of nature-based and/or protected area tourism have been developed in recent decades. One of the most widely used methodologies are variants of the Money Generation Model (MGM) that was originally developed for the US National Parks (NPs). This methodology was piloted in Iceland at the Snæfellsjökull NP in 2017, and larger study covering 11 other sites was conducted in 2018 (Siltanen, 2017 & 2018). These studies showed that the economic and employment impacts of most sites in the studies were high and that nature-based tourism also contributed a significant amount of tax revenue to the state. This report presents an economic impact study of the Hafnarhólmi bird colony, a protected breeding area especially famous for puffins in the remote East Iceland community of Borgarfjörður Eystri. The results of the study are interesting for two reasons; this is the first time the MGM methodology is used in Iceland to measure the economic impact of a bird-watching site, and second, the remoteness of the Borgarfjörður Eystri community allows for a focused analysis of the economic and employment impacts to a small community. Regardless of the tourism boom, small rural communities in Iceland have been struggling with declines of economic opportunities and populations, and research methods that could indicate new sources of income and opportunities are needed. In part supporting these efforts, this study received partial grant funding from Iceland's Fragile Communities program and the Ministry of the Environment and Natural Resources; and volunteer work effort from the Royal Society for the Protection of Birds (RSPB). The results of the study indicate that the local economic effects of the Hafnarhólmi bird colony are relatively modest in comparison to local effects at other sites in the previous studies. This is mainly due to undeveloped tourism services locally and short stays of the visitors. However, overall economic effects that also account for the visitors' spending outside the immediate vicinity are comparable to previous studies, suggesting that bird-watching sites have similar economic potential as other nature sites. Several suggestions on how to increase the local economic impacts are also provided based on the observed visitor behavior and spending during the study.
Keywords: 330; ecotourism; regional growth; employment effect; Iceland; Ökotourismus; Regionales Wachstum; Beschäftigungseffekt; Island